Analysis of surface runoff water and sediment generations using a short-term water budget in the steeply sloping agricultural land of northern Laos. Issue 4 (4th July 2021) - Kohmoto, Yuko; Watanabe, Tetsuhiro; Sipaseuth, Nivong; Funakawa, Shinya
ABSTRACT: A field experiment was conducted during the rainy season of 2014, in the steeply sloping agricultural land of northern Laos to determine the factors that cause the generation of surface runoff water and sediment (i.e., soil erosion). Four treatments (upland rice cropping, maize cropping, maize cropping with mulch treatment, and bare land) were installed on a 2 square meters plot sloping 25°, or 45%. The surface runoff water was measured at 10 min intervals, and the total eroded water and sediment were collected after each rainfall event. The total rainfall during the experiment was 1, 480 mm, equivalent to more than 80% of the annual rainfall, with the largest rainfall of 413 mm occurring in July. Strong rainfall, exceeding 10 mm in 10 min, occurred frequently (26 times). More than 50% of the surface runoff water and sediment were generated during the mid-rainy season. Short-term water budget analysis revealed that the amount of the surface runoff water and sediment depended on the soil surface conditions and the initial volumetric water content of the soil. Specifically, 1) rapid water infiltration and percolation suppress the surface runoff water and sediment during the early rainy season, 2) water saturation in the surface soil, clogging of soil pores, and sealing induce soil loss during the mid-rainy season, and 3) crust formation and/or clogging of soil pores induces surface runoff during the late rainy season. Mulching suppressed surface runoff generation by facilitating water infiltration into the soil and mitigating the disturbance of the soil surface by raindrops.